The organizational competences model: a contribution for business-IT alignment - Malta, Pedro Maia (2011)
Business-IT alignment has consistently ranked in the top five IT management concerns for almost a decade now. Despite a considerable research since the 90s, business-IT alignment still remains a challenge even more in turbulent organizational environments requiring business strategy to be more frequently examined and changed. We need effective ways to achieve and sustain alignment between the information systems and technology strategy and the business strategy so organizations become more flexible and agile. Enterprise architecture may be one of those effective ways particularly when developed under a business process management approach. Looking into a consulting practice that has adopted such approach, this research highlights the role of one particular model, the organizational competences model, in the clarification of the strategy and in the development of the enterprise architecture for a wine regulatory commission, the organization that was used as a case study.